Comparative evaluation of flow boiling heat transfer characteristics of R-1234ze(E) and R-134a in plate heat exchangers with different Chevron angles. (5th March 2018) - Kim, Dongwoo; Lee, DongChan; Jang, Dong Soo; Jeon, Yongseok; Kim, Yongchan
Highlights: The flow boiling heat transfer characteristics of R-1234ze(E) and R-134a in plate heat exchangers are measured and analyzed. The heat transfer coefficients of R-1234ze(E) and R-134a are quite similar at the same mass flux. R-1234ze(E) shows higher pressure drop than R-134a owing to the lower vapor density. The correlations for the heat transfer and pressure drop of R-1234ze(E) are developed considering different Chevron angles. Abstract: In this study, the flow boiling heat transfer characteristics of R-1234ze(E) and R-134a in plate heat exchangers with different Chevron angles are measured and analyzed as a function of the mass flux, saturation temperature, vapor quality, and heat flux. The effect of the mass flux on the heat transfer and pressure drop of R-1234ze(E) is substantial. The heat transfer coefficient of R-1234ze(E) for a Chevron angle of 60° is approximately 3.7 times higher than that for a Chevron angle of 30° at high vapor qualities owing to the intensified turbulent flow. Moreover, for a Chevron angle of 60°, the average heat transfer coefficient of R-1234ze(E) is on average 4.7% higher than that of R-134a due to its higher equivalent Reynolds number. However, the average pressure drop of R-1234ze(E) is higher than that of R-134a owing to the lower vapor density of R-1234ze(E). Finally, the correlations for the heat transfer and pressure drop of R-1234ze(E) are developed in the plate heat exchangers with different Chevron angles.